2017
DOI: 10.1107/s2052520616018266
|View full text |Cite
|
Sign up to set email alerts
|

Structure, thermal expansion and incompressibility of MgSO4·9H2O, its relationship to meridianiite (MgSO4·11H2O) and possible natural occurrences

Abstract: We have employed neutron and X-ray powder diffraction and density functional theory calculations to determine the structure and thermoelastic properties of a new hydrate in the MgSO4–H2O binary system, magnesium sulfate enneahydrate. We show that this 9-hydrate could occur naturally in certain hypersaline lakes on Earth and indicate where it may be formed as a more persistent mineral elsewhere in the solar system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 81 publications
4
18
0
Order By: Relevance
“…We will compare now the compressibility of chalcomenite with related hydrated oxides. The obtained bulk modulus is similar to that of FeSO4•H2O (45 GPa) [12], MgSO4·9H2O (50 GPa) [35], and CaSO4•2H2O (44 GPa) [36]. It is known that hydrated oxides are more compressible than their dehydrated counterparts [37].…”
Section: Equation Of Statessupporting
confidence: 68%
“…We will compare now the compressibility of chalcomenite with related hydrated oxides. The obtained bulk modulus is similar to that of FeSO4•H2O (45 GPa) [12], MgSO4·9H2O (50 GPa) [35], and CaSO4•2H2O (44 GPa) [36]. It is known that hydrated oxides are more compressible than their dehydrated counterparts [37].…”
Section: Equation Of Statessupporting
confidence: 68%
“…Tick marks for NiSO 4 •9D 2 O are uppermost and those for water ice are below them Tests for convergence of the total energy and of structural parameters were done by varying the basis-set cut-offs and the reciprocal-space sampling. As described in our earlier paper (Fortes et al 2017b), we found that the recently developed Wu-Cohen GGA functional (Wu and Cohen 2006) gives more accurate structural parameters than PBE for these materials, changing the ~ 5% over-estimation of molar volume to a ~ 1% under-estimation.…”
Section: Density Functional Theory Calculationssupporting
confidence: 65%
“…The DFT + U calculations yield S-O and Ni-O distances that are longer than the experimental values and so the polyhedral volumes are too great by 3-5%. This is not a deficiency of the spin-polarised calculations or the adopted value of U eff , since the same differences were observed in MgSO 4 •9H 2 O (Fortes et al 2017b). Further comparisons will be made in the context of the 9-hydrate structure in the following section.…”
Section: Structure Determination and Completion (8-hydrate)mentioning
confidence: 92%
See 2 more Smart Citations